Mesangiogenic Progenitor Cells Are Tissue Specific and Cannot Be Isolated From Adipose Tissue or Umbilical Cord Blood - Barachini, Serena; Montali, Marina; Panvini, Francesca M.; Carnicelli, Vittoria; Gatti, Gian Luca; Piolanti, Nicola; Bonicoli, Enrico; Scaglione, Michelangelo; Buda, Gabriele; Parchi, Paolo D. (Frontiers in Cell and Developmental Biology, 2021)
Mesangiogenic progenitor cells (MPCs) have been isolated from human bone marrow mononuclear cells (BM-MNCs). They attracted particular attention for the ability to differentiate into exponentially growing mesenchymal stromal cells (MSCs) while retaining endothelial differentiative potential. MPC power to couple mesengenesis and angiogenesis, highlights their tissue regenerative potential and clinical value, with particular reference to musculoskeletal tissues regeneration. BM and adipose tissue (AT) represent the most promising adult multipotent cell sources for bone and cartilage repair, although discussion is still open on their respective profitability. Culture determinants as well as tissues of origin appeared to strongly affect the regenerative potential of cell preparations, making reliable methods for cell isolation and growth a prerequisite to obtain cell-based medicinal products (CMBPs). Our group had established a definite consistent protocol for MPC culture and here we present data showing MPCs to be tissue specific.